2022
DOI: 10.21037/jtd-22-1122
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier dysfunction is involved in the development of systemic inflammatory responses and lung injury in type A aortic dissection: a case-control study

Abstract: Background: The definite pathogenesis of lung injury complicated by type A aortic dissection (TAAD) remains unclear. In this paper, we investigated the relationship between intestinal injury, lung injury, and systemic inflammatory responses, with the aim of exploring the mechanism underlying intestinal injury and its impact on systemic inflammatory responses and lung injury in patients with TAAD.Methods: Patients with TAAD (n=36) and those with aortic root aneurysm (ARA) (n=30) were compared.TAAD patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…IL-6 and TNF-α are markers of immune activation and have been implicated in signalling immune reactions during the PSD process. These cytokines may also interact with iFABP, potentially leading to gut permeability and subsequent immune and inflammatory responses [13] [14] . David et al [15] demonstrated that patients with spinal cord injuries have elevated levels of IL-6, TNF-α, and iFABP, which are associated with increased gut barrier damage.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 and TNF-α are markers of immune activation and have been implicated in signalling immune reactions during the PSD process. These cytokines may also interact with iFABP, potentially leading to gut permeability and subsequent immune and inflammatory responses [13] [14] . David et al [15] demonstrated that patients with spinal cord injuries have elevated levels of IL-6, TNF-α, and iFABP, which are associated with increased gut barrier damage.…”
Section: Introductionmentioning
confidence: 99%